Dielectric and microwave absorption properties of AlN‐SiBCN lossy ceramics. Issue 2 (10th September 2017) - He, Yongqin; Li, Xiaoyun; Zhang, Jingxian; Li, Xiaoguang; Yu, Mingxian; Duan, Yusen; Jiang, Dongliang; Qiu, Tai
Abstract: Dense AlN‐SiBCN ceramics were fabricated by pyrolysis of a commercially available polyborosilazane followed by hot‐pressing of AlN and SiBCN mixture in N2 atmosphere. The effect of SiBCN content on phase behavior, microstructure, electrical conductivity, dielectric and microwave absorption properties of the composites were investigated. The results showed that characteristic peaks of Si3 N4, SiC, and BNC appeared above 1650°C during the annealing of SiBCN powder. The composites fabricated with 30 wt.% SiBCN had the highest electrical conductivity and dielectric permittivity, which can be attributed to the formation of SiC nanoparticles. With further increase in SiBCN content, the composites showed the lowest reflection coefficient of −30.88 dB at 8.5 GHz and the frequency bandwidth of 1 GHz below −10 dB in X‐band.